The decision of breastfeeding practices among parents attending primary health care facilities in suburban Malaysia - Draman, Nani; Mohamad, Noraini; M. Yusoff, Harmy; Muhamad, Rosediani (Taibah University, Madinah, Kingdom of Saudi Arabia, 2017)
Objectives: This study aimed to determine the association between decision making for breastfeeding practices and associated factors for exclusive breastfeeding practices among parents attending primary health care facilities. Methods: This cross-sectional study involved 196 parents who attended primary health care facilities in suburban Malaysia. A self-administered questionnaire was given to assess decision-making styles and factors associated with exclusive breastfeeding practices. Systematic random sampling was used for the nonexclusive breastfeeding group, and convenience sampling was used for the exclusive breastfeeding group. Multiple logistic regression analysis was conducted to determine the associated factors for exclusive breastfeeding practices. Results: We found an association between the mutual decision of parents on exclusive breastfeeding and exclusive breastfeeding practices. Previous exclusive breastfeeding experience, fathers’ ages, mothers’ occupations and mutual decisions had significant impact on exclusive breastfeeding practices. Conclusion: The important determinant for practising exclusive breastfeeding is parents’ mutual decisions. Therefore, practitioners need to continuously educate and emphasize the fathers’ role in the breastfeeding process.